Kesulitan Konseptual Mahasiswa PGMI terhadap Bilangan Bulat dan Implikasinya bagi Kesiapan Mengajar Matematika - Arief, Arief Arafat Hankam (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
Understanding the concept of integers is a basic competency that prospective Madrasah Ibtidaiyah (MI) teachers must possess. However, many PGMI students still experience difficulties in mastering this concept in depth, which has the potential to hinder their readiness to teach mathematics at the elementary level. This study used a descriptive qualitative approach involving 15 sixth-semester PGMI students as participants. Data were collected through open- ended diagnostic tests, in-depth interviews, and document analysis of lesson plans. Data analysis techniques employed the Miles and Huberman model, including data reduction, data presentation, and drawing conclusions. The results of the study indicate that students experience difficulties in understanding the meaning of negative numbers, mixed operations with integers, and the use of number line representations. These misconceptions result in inaccuracies in developing learning strategies, low self-confidence when teaching, and an inability to explain concepts coherently to students. These findings highlight the importance of conceptual reinforcement in basic mathematics education at PGMI, as well as the need for a more applied and contextual approach in teaching integer concepts. Recommendations are directed toward the development of conceptual learning modules based on problem-solving and visual representations.